Valorisation of Rice Husk and Bubble Wrap Plastic Waste through Co-Torrefaction to Optimise Biochar Production - Aloysius Gonzaga Holy Prajitna; Mochammad Chaerul (Jurnal Ilmu Lingkungan, 2024)
Rice husk is one of the highest generated agricultural waste estimated to be 11.1-13.8 million tons in Indonesia in 2021. This quantity makes rice husk a potential biomass for conversion into energy to minimize the negative impacts of current processing methods, such as open-burning and mulching. Torrefaction was conducted at 300°C for 30 minutes in this study to enhance the characteristics of biomass fuel by producing biochar with improved combustion properties. The biochar produced from torrefaction of rice husk has a calorific value of 15.04 MJ/kg with a volatile matter content of 42.94% and fixed carbon content of 17.94%. Despite this improvement compared to raw rice husk, this biochar tends to have a relatively high mass loss, with a mass yield of only 54%. Therefore, the addition of LDPE plastic feedstock in the form of bubble wrap was carried out up to 50% of the feedstock mass, resulting in further optimization at the RH50 variation, which increased the calorific value to 19.98 MJ/kg and mass yield to 72%. These changes were statistically tested and found to be significant, indicating that torrefaction is a promising technology for rice husk processing, and bubble wrap in this study can significantly contribute to enhancing the characteristics of rice husk as a renewable fuel source.